Stable Fly Stomoxys calcitrans (L.) (Insecta: Diptera: Muscidae) - Phillip E. Kaufman; Edwin R. Burgess IV; Emma N. I. Weeks (EDIS)
Updated by Edwin R. Burgess IV. Originally written by Phillip E. Kaufman and Emma N. I. Weeks,  January 2016.